Strengthening the Role of Nurses in Managing Respiratory Problems in Infants with Bronchiolitis: A Literature Review - Siagian , Kezia Octavina; Juliani, Angelica; Permaida, Permaida; Zendrato, Meylona Verawati (Inspirasi Foundation, 2026)
Introduction: Bronchiolitis is a major cause of hospitalization in infants and remains a leading respiratory challenge in paediatric care worldwide. Triggered mainly by the Respiratory Syncytial Virus (RSV), this condition causes airway inflammation, mucus obstruction, and respiratory distress that can rapidly progress to oxygenation failure. While most cases are self-limiting, inadequate nursing interventions often lead to prolonged illness and complications. Therefore, implementing evidence-based nursing strategies, including observation, education, therapeutic, and collaborative approaches, is essential to ensure comprehensive respiratory management and faster recovery in affected infants. Objective: This study aims to analyse the implementation of nursing care strategies through observation, education, therapeutic, and collaborative approaches to optimize respiratory management and recovery in infants with bronchiolitis. Method: This study used a literature review design by analysing six relevant articles published between 2021 and 2025 obtained from Google Scholar. The literature selection followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, focusing on the implementation of nursing strategies in managing respiratory problems in bronchiolitis. Result: The review found that observation was the most frequently applied nursing intervention, serving as the foundation for assessing physiological responses. Therapeutic and collaborative actions, such as chest physiotherapy, semi-fowler, positioning, nebulization, and oxygen therapy, were effective in improving oxygen saturation and reducing respiratory effort. Educational interventions, although less common, significantly strengthened family involvement and awareness of home care practices. The integration of these four strategies enhanced recovery, improved comfort, and demonstrated measurable clinical benefits for infants with bronchiolitis. Conclusion: The balanced and evidence-based application of observation, education, therapeutic, and collaborative strategies strengthens nursing care quality, accelerates respiratory recovery, and reinforces the nurse’s essential role in holistic management of bronchiolitis